Evaluación De Tres Niveles De Mananos Oligosacáridos (Sacharomices Cerevisae) En Los Parámetros Productivos Y Salud Intestinal En Pollos De Engorde En El Cantón Babahoyo, Provincia De Los RÃos, Ecuador - Moreira, Ricardo Zambrano; Villalva, Juan Carlos Gómez; Ãlava, Johns RodrÃguez; Ãlvarez, Hugo Alvarado; Gallardo, Luis Quezada; Hurtado, William Filian; Cepeda, Edison Ponce; Cevallos, Juan Avellaneda (European Scientific Journal, ESJ, 2017)
The objective of this research was to evaluate different levels of mannans oligosaccharides (MOs) in productive parameters and intestinal health in broilers. Two hundred and forty one-day-old broiler chickens (Ross 308 line) were used during a 6-week experimental period. A completely randomized design with four treatments and six replicates was used. The evaluated levels were 0.0 kg t-1 (T0); 0.5 kg t-1 (T 1); 1 kg t-1 (T2) and 1.5 kg t-1 (T3). For the mean comparisons, a Tukey test (P≤0.05) was used. The source of oligosaccharide mannans derived from the cell wall of Saccharomyces cerevisiae and it was added to the commercial balanced feed. Productive parameters, intestinal villi and economic performance (costbenefit) were evaluated. The data was analyzed with the statistical program SAS V9 (2012). At 42 days of the test, T2 reached the highest average weight of 2455.48 g. For feed consumption, the mean average for T0, T1, T3 and T2 were 4342.63 g, 4304.5 g, 4254.32 g and 4216.80 g respectively. T2 had higher weight gain compare to the control group, 535.70 and 388.84 g, respectively. Feed conversion was higher for T2 (1.71) compared to the control group (1.85). T1 obtained had a carcass yield of 75.89%. Mortality did not show significant differences (P≥ 0.05). Length and width (μm) of the intestinal villi were different (P≤0.05) among treatments, at 21 days of, T3 showed the longest (1939.74 μm) and widest (326.03 μm) measures at the duodenum site. The economic analysis, all the treatments were profitable results, although T1 had the highest cost-benefits ( 1.30).